Mutations in the thyrotropin receptor signal transduction pathway in the hyperfunctioning thyroid nodules from multinodular goiters: A study in the Turkish population - GÖZÜ, HÜLYA (JAPAN ENDOCRINE SOC, 2005)
Many studies have been carried out to determine G(s)alpha and TSHR mutations in autonomously functioning thyroid nodules. Variable prevalences for somatic constitutively activating TSHR mutations in hot nodules have been reported. Moreover, the increased prevalence of toxic multinodular goiters in iodine-deficient regions is well known. In Turkey, a country with high incidence rates of goiter due to iodine deficiency, the frequency of mutations in the thyrotropin receptor signal transduction pathway has not been evaluated up to now. In the present study, a part of the genes of the TSHR, G(s)alpha and the catalytic subunit of the PKA were checked for activating mutations. Thirty-five patients who underwent thyroidectomy for multinodular goiters were examined. Genomic DNAs were extracted from 58 hyperactive nodular specimens and surrounding normal thyroid tissues. Mutation screening was done by single-strand conformational polymorphism (SSCP) analysis. In those cases where a mutation was detected, the localization of the mutation was determined by automatic DNA sequencing. No G(s)alpha or PKA mutations were detected, whereas ten mutations (17%) were identified in the TSHR gene. All mutations were somatic and heterozygotic. In conclusion, the frequency of mutations in the cAMP signal transduction pathway was found to be lower than expected in the Turkish population most likely because of the use of SSCP as a screening method and sequencing only a part of TSHR exon 10.
Keywords: thyroid nodules; thyrotropin receptor; G(S)alpha gene; protein kinase A gene; mutations; SOMATIC MUTATIONS; TSH RECEPTOR; GEL-ELECTROPHORESIS; ONCOGENIC MUTATIONS; CATALYTIC SUBUNIT; POINT MUTATIONS; TOXIC ADENOMA; GENE; G(S)ALPHA; PREVALENCE